Ambientes de aprendizaje en el desarrollo cognitivo de los niños de educación inicial, subnivel 2 de la Unidad Educativa Zapotal - Alvarado Contreras, Leydi Dayana (2023)
The case study deals with the learning environments and the cognitive development of children in initial education. The objective of the work is to analyze the learning environment in the cognitive development of children in initial education, Sublevel 2 of the Zapotal Educational Unit. The methodology consisted of a mixed approach, descriptive and documentary research, interview and observation technique with their respective instruments, which were addressed to a sample of 35 children and 1 Sublevel 2 initial education teacher. The results were that, a significant percentage of children do not yet have adequate cognitive development, since it is difficult for them to share learning experiences with their peers, participate actively, solve problems and establish differences in images or objects. The teacher has basic knowledge about learning environments, the main drawbacks for an adequate learning environment is the limitation of resources, behavior and motivation of the students, the educator uses different strategies within the environments such as reading, singing or playful activities. As conclusions, the learning environment in initial education children is important for their comprehensive development, since this physical and social space allows infants to interact, explore, acquire skills and knowledge, which are essential for the development of activities in futures. degrees. The cognitive development acquired by children in Sublevel 2 initial education is good, however, in some infants there are important weaknesses because they have not been able to develop certain cognitive abilities.